GAS CHROMATOGRAPHY-MASS SPECTROSCOPY ANALYSIS OF PHYTOCHEMICAL CONSTITUENTS OF METHANOLIC EXTRACT OF NEEDLES OF PINUS WALLICHIANA - JOSHI, SWATI; RAI, NISHANT; Kumar, Navin (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To investigate the phytoconstituents of methanolic extracts of a conifer Pinus wallichiana using gas chromatography-mass spectroscopy (GC-MS), which is famous for its timber quality, resins and oils. Methods: The present investigation was carried out to determine the possible chemical constituents present in the methanolic extracts in the needles of P. wallichiana. Results: The result of the GC-MS confirmed the presence of 38 compounds. Momeinositol (43.27%), 9, 12-octadecanoic acid, 2 (12.52%) pentadecanoic acid (4.12%) and dibutyl phthalate (3.34%) were the major compound found through the GC-MS analysis. Conclusion: The presence of various compounds in the methanolic extract of P. wallichiana confirms its relevance not only for pharmaceutical purpose but for various industrial purposes too. Keywords: Pinus wallichiana, Gas chromatography-mass spectroscopy (GC-MS), Gas chromatography-mass spectroscopy of plant extract, Gas chromatography-mass spectroscopy of conifer, Gas chromatography-mass spectroscopy profiling.